2016
DOI: 10.1139/cjps-2016-0130
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between Cultivars of Legumes Species (Trifolium pratense L., Medicago sativa L.) and Grasses (Phleum pratense L., Lolium perenne L.) Under Different Nitrogen Levels

Abstract: ARTICLEInteractions between cultivars of legume species (Trifolium pratense L., Medicago sativa L.) and grasses (Phleum pratense L., Lolium perenne L.) under different nitrogen levels Abstract: The transfer of nitrogen (N) from legumes to grasses is an important process in low-input forage production systems, and may be improved by selecting compatible species and cultivars. This study sought to examine what effect species and cultivar have on plant growth and N accumulation in temperate grass-legume mixtures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 48 publications
1
10
0
Order By: Relevance
“…However, in a continental-scale field study with two perennial N 2 -fixing legumes (red clover and white clover) and four perennial grasses (perennial ryegrass, Timothy (Phleum pratense L.), Kentucky bluegrass, and orchardgrass (Dactylis glomerata L.)), it was reported that N gained in mixed swards increased with increasing legume proportion up to 30% [71]. This supports the assertion by [26] that grass N demand in grass-legume mixtures might be more important than legume N supply in determining N transfer efficiency. In an annual garden pea-barley intercropping system, greatest N transfer was obtained in 1:1 garden pea: barley compared to 2:1 system [72].…”
Section: Factors Affecting Nitrogen Transfersupporting
confidence: 75%
See 2 more Smart Citations
“…However, in a continental-scale field study with two perennial N 2 -fixing legumes (red clover and white clover) and four perennial grasses (perennial ryegrass, Timothy (Phleum pratense L.), Kentucky bluegrass, and orchardgrass (Dactylis glomerata L.)), it was reported that N gained in mixed swards increased with increasing legume proportion up to 30% [71]. This supports the assertion by [26] that grass N demand in grass-legume mixtures might be more important than legume N supply in determining N transfer efficiency. In an annual garden pea-barley intercropping system, greatest N transfer was obtained in 1:1 garden pea: barley compared to 2:1 system [72].…”
Section: Factors Affecting Nitrogen Transfersupporting
confidence: 75%
“…Compatibility of species grown in mixed swards affects the amount of N 2 fixed and the proportion transferred. A recent study has shown that grass N demand in grass-legume mixtures might be more important than legume N supply in determining N transfer efficiency [26].…”
Section: Factors Affecting Nitrogen Transfermentioning
confidence: 99%
See 1 more Smart Citation
“…Legume-grass mixtures for forage often contain red clover (Trifolium pratense), alfalfa (Medicago sativa), and different grass species adapted to regional conditions (e.g., Braun et al [57], Biewer et al [58], McElroy et al [59], Sleugh et al [60]). The species combination can be adjusted for different environmental conditions and aims, such as aboveground biomass, feed quality, and preceding crop effect (belowground biomass, nitrogen or carbon balance) by varying the shares of grasses and legumes [61].…”
Section: Examples Of Perennial Polyculturesmentioning
confidence: 99%
“…A very high proportion of grasses in the mixture exhibits a high carbon capture rate, but results in a poor trade-off with the nitrogen balance, whereas a mixture with a high proportion of legumes in the seed (≥80%) exhibits high carbon capture rates and fixes more nitrogen, up to 540 kg N/ha per year [61]. The N accumulation from the grass component of the mixture is also important for the soil fertility increase, and appears to be influenced more by the grass N demand than the legume N supply [59]. The effects of perennial legume cultivation on the subsequent crops are apparent until the third and fourth year [48,78].…”
Section: Soil Fertilitymentioning
confidence: 99%